2008
DOI: 10.3182/20080706-5-kr-1001.00448
|View full text |Cite
|
Sign up to set email alerts
|

A Probabilistic Algorithm for Mode Based Motion Planning of Agile Unmanned Air Vehicles in Complex Environments

Abstract: Abstract:In this work, we consider the design of a probabilistic trajectory planner for a highly maneuverable unmanned air vehicle flying in a dense and complex city-like environment. Our design hinges on the decomposition of the problem into a) flight controls of fundamental agile-maneuvering flight modes and b) trajectory planning using these controlled flight modes from which almost any aggressive maneuver (or a combination of) can be created. This allows significant decreases in control input space and thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…LoS-Check helps the planners generate better solutions at a faster speed, but it could still be improved. There are also many other path optimization methods similar to LoS-Check [40][41][42].…”
Section: Related Work and Motivationmentioning
confidence: 99%
“…LoS-Check helps the planners generate better solutions at a faster speed, but it could still be improved. There are also many other path optimization methods similar to LoS-Check [40][41][42].…”
Section: Related Work and Motivationmentioning
confidence: 99%
“…The algorithm envisioned is to use the TCAS solution as the initial solution and further improve on it. In our earlier work [17][18][19][20], we observed that before the major feasible path planning phase, defining the geometrical obstacle free path and tractable way points significantly accelerates the searching ability and decreases the total computational time of planner. This approach is considered to be implemented, is into two layers.…”
Section: Real-time 4d Trajectory Planning For Pilot Decision Supportmentioning
confidence: 99%